Intensified research on tuberculosis in the Western Pacific Region: a bibliometric analysis, 2000-2019 - Fukushi Morishita; Takuya Yamanaka; Tauhid Islam (World Health Organization Regional Office for the Western Pacific, 2020)
"Intensified TB research and innovation" is one of the three pillars of the End TB Strategy. To assess achievements and gaps in tuberculosis (TB) research productivity in countries and areas of the Western Pacific Region quantitatively, a bibliometric analysis was carried out by examining trends in the numbers of publications on TB indexed in PubMed between 2000 and 2019 and by comparing them with trends in publications on other selected major infectious diseases for the same period. The number of publications on TB in the Region increased by 3.2 times during the period, from 534 in 2000-2004 to 1714 in 2015-2019, as compared with 2.9 times each for HIV, hepatitis and malaria. The number increased by 46% in 2005-2009, 79% in 2010-2014 and 23% in 2015-2019, as compared with each previous 5-year period. The average annual growth rate between 2000 and 2018 was 8.8%. China accounted for 34.8% of the total number of publications on TB in the Region. Increases in TB research were observed in most countries and areas in the Region, particularly in those with a high TB burden. The number of publications on TB remained low, however, in the Lao People's Democratic Republic, Mongolia and Pacific island countries. Countries are encouraged to implement the set of actions proposed in the Global Strategy for TB Research and Innovation to accelerate progress towards ending TB.